2020
DOI: 10.1108/pijpsm-05-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of police behaviors in the disaster COVID-19 – The case of Serbia

Abstract: PurposeThe aim of the study is to determine the perception of general public on the Serbian police behaviors in combating COVID-19 pandemic, as well as the perception of the citizens how successful the police units were in fulfilling their tasks.Design/methodology/approachDue to the state of emergency declared due to COVID-19 pandemic, in particular the restriction of movement and the need for social distance, the data collection for this study had to be conducted via the online survey platform (Google.doc). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…When the pandemic first broke out in Serbia, the first action was to restrict all border crossings with neighboring countries, as had been done in other European countries. Citizens who obtained a self-isolation order or an epidemiologist’s order due to COVID-19 concerns or suspicions of contact with a sick person were required to stay at home for 14 or 28 days [ 84 ]. According to official data (updated on 12 September 2021) of the Institute of Public Health of Serbia, Dr Milan Jovanović Batut of the WHO stated that the total numbers infected were 1,270,407, hospitalized 3511, the number of people on respirators 197, the total number of deaths 12,075, mortality rate 0.95% and the total number tested 6,941,684 [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…When the pandemic first broke out in Serbia, the first action was to restrict all border crossings with neighboring countries, as had been done in other European countries. Citizens who obtained a self-isolation order or an epidemiologist’s order due to COVID-19 concerns or suspicions of contact with a sick person were required to stay at home for 14 or 28 days [ 84 ]. According to official data (updated on 12 September 2021) of the Institute of Public Health of Serbia, Dr Milan Jovanović Batut of the WHO stated that the total numbers infected were 1,270,407, hospitalized 3511, the number of people on respirators 197, the total number of deaths 12,075, mortality rate 0.95% and the total number tested 6,941,684 [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…The researchers found a rise in trust in the police and the government during the lockdown, concluding that these ‘effects are consistent with the concept of “rallying around the flag”’ ( Sibley et al , 2020 , p. 626). In Serbia, Janković and Cvetković (2020) conducted an online survey 4 weeks after the state of emergency was declared. They found that even when participants perceived the police as being underprepared for the crisis, their trust in the police was high.…”
Section: Public Attitudes Towards the Police And Crisis Situationsmentioning
confidence: 99%
“…There are only a few studies that have examined the public's view of how well the police performed their new COVID-19 duties (Caluori & Clements, 2020;Janković & Cvetković, 2020;Laufs & Waseem, 2020;Wallace et al, 2022). For instance, Janković and Cvetković (2020) conducted an online survey of public perceptions of the Serbian police during the COVID-19 pandemic and found that the public was happy with police performance during the COVID-19 pandemic.…”
Section: Public Perception Of Police Performance During Covid-19mentioning
confidence: 99%